Creating new teaching contents with a design approach. How the use of design methodologies based on professional experiences can be used to create successful courses in a limited timeframe - Kiko Gaspar Quevedo; José Miguel Abarca Fernández (Multidisciplinary Journal for Education, Social and Technological Sciences, 2023)
The aim of this paper is to analyze and evaluate the effectiveness of the use of design thinking and other design methodologies to address the creation and implementation of a new subject in the Design Engineering and Product Development degree at the Polytechnic University of Valencia (UPV).